Interacting effects of climate and landscape physiography on piñon pine growth using an individual‐based approach. Issue 3 (10th March 2017) - Redmond, Miranda D.; Kelsey, Katharine C.; Urza, Alexandra K.; Barger, Nichole N.
Abstract: Forest and woodland ecosystems play a crucial role in the global carbon cycle and may be strongly affected by changing climate. Here, we use an individual‐based approach to model piñon pine ( Pinus edulis ) radial growth responses to climate across gradients of environmental stress. We sampled piñon pine trees at 24 sites across southwestern Colorado that varied in soil available water capacity (AWC), elevation, and latitude, obtaining a total of 552 piñon pine tree ring series. We used linear mixed‐effect models to assess piñon pine growth responses to climate and site‐level environmental stress (30‐year mean cumulative climatic water deficit [CWD] and soil AWC). Using a similar modeling approach, we also determined long‐term growth trends across our gradients of environmental stress. Piñon pine growth was strongly positively associated with winter precipitation. Summer vapor pressure deficit (VPD) was strongly negatively associated with piñon pine growth during years of low winter precipitation, whereas summer VPD had no effect on piñon pine growth during years of high winter precipitation. The strength of the relationship between the annual climatic variables (winter precipitation and summer VPD) and piñon pine growth was also influenced by site‐level environmental stress, suggesting that the sensitivity of woodland ecosystems to changing climate will vary across the landscape due to differences in local physiographic conditions. Trees at sites with lower CWDs were more responsive to summer VPD, showing greater reductions in growth rates during warmer years. Trees at sites with greater soil AWC were more responsive to winter precipitation, showing higher growth rates during years of high precipitation. Piñon pine growth rates declined moderately over the past century across our study area, suggesting that recent increases in aridity have resulted in long‐term growth declines.